2014
DOI: 10.1371/journal.pone.0101390
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Pathological Features and Prognosis of Invasive Micropapillary Carcinoma Compared to Invasive Ductal Carcinoma: A Population-Based Study from China

Abstract: BackgroundInvasive micropapillary carcinoma (IMPC) of the breast is a rare subtype of breast cancer that is associated with a high incidence of regional lymph node metastases and a poor clinical outcome. However, the clinico-pathological features and prognostic factors of IMPC are not well understood.Patients and MethodsA total of 188 IMPC cases and 1,289 invasive ductal carcinoma (IDC) cases were included. The clinical features, breast cancer-specific survival (BCSS) and recurrence/metastasis-free survival (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
40
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 22 publications
11
40
1
6
Order By: Relevance
“…These results are consistent with previous study reported that IDC is the most common histological type of invasive breast cancer [18]. In accordance, EL-Fiky et al, 2015 [19] reported that 98% of the breast cancer cases were IDC with the age ranged from >35 to 55 years and the tumor size from >2 to 5 cm were seen in 73% of malignant cases.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with previous study reported that IDC is the most common histological type of invasive breast cancer [18]. In accordance, EL-Fiky et al, 2015 [19] reported that 98% of the breast cancer cases were IDC with the age ranged from >35 to 55 years and the tumor size from >2 to 5 cm were seen in 73% of malignant cases.…”
Section: Discussionsupporting
confidence: 92%
“…7,[14][15][16][17]23,24,[37][38][39][40][41][42][43] One study of 624 patients with IMPC revealed a poor prognosis in the patients who had a tumor lacking in estrogen receptor expression. 7 The status of the HER2/neu protein expression or gene amplification in IMPC is not consistent in literature.…”
Section: Immunophenotypementioning
confidence: 99%
“…34,38,41,44 Regarding the molecular classification, more cases of IMPC fall into the luminal A and luminal B subtypes than they do with IDC-NOS. 39 The features of IMPC are summarized in the Table. In addition, IMPC should be differentiated from IDC-NOS by retraction artifacts. Immunohistochemistry for epithelial membrane antigen and sialyl Lewis X, highlighting the apical cellular membrane of peripheral cells at the tumor nests, confirms the diagnosis.…”
Section: Immunophenotypementioning
confidence: 99%
“…Several studies compared their cohort of IMPC patients to invasive ductal carcinoma (IDC) controls matched by disease stage and revealed a significantly higher incidence of lymph node metastasis in IMPC patients, particularly for early stage breast cancer [9][10][11][12]14,[23][24][25]28,31,32]. Yu [19-21] b Case series 68 68 NA Tressera et al [26] Case series 15 15 NA Middleton et al [22] Case series 14 14 NA Walsh and Bleiweiss [29] Case series 80 80 "Pure" (n =17), "partial" (n =63, range 5-95%) Wei et al [30] Case series 100 100 475% (n= 42), 50-75% (n=20), 25-50% (n =15), o25% (n=23) Varga et al [27] Case series 11 11 NA Li et al [18] Case series 40 40 "Pure" (n =9), "mixed" (n =31) Chen et al [14] Case series 100 100 NA Shi et al [25] Case series 188 188 "Pure" (n =27), "mixed" (n= 161) Kim et al [11] Cohort 250 38 450% (n= 17), o50% (n =21) Nassar et al [12] Cohort 1400 83 480% (n= 10), "minor proportion" (n =73) Kuroda et al [17] Cohort 671 27 "Some" De La Cruz et al [15] Cohort 1056 16 "Pure" (n =10), "mixed" (n= 6) Zekioglu et al [32] Cohort 2022 53 475% (n= 47), o75% (n =6) Pettinato et al [13] Cohort 1635 62 50-100% (n =40), 25-50% (n =12), o25% (n=10) Yu et al [31] Cohort 2753 72 470% (n= 72) Vingiani et al [28] Cohort 13,278 49 "Pure" (n =49) Paterakos et al [23] Cohort 1287 21 "Pure" (n =21) Gocke et al [10] Cohort 2718 103 "Pure" (n =20), "mixed" (n= 83) Ren et al [24] Cohort 5625 86 NA Chen et al [8,9] however no difference was seen on overall survival analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al [25] compared 188 IMPC patients to 1289 unmatched controls with IDC. They demonstrated worse recurrence free survival (p= 0.034) and breast cancerspecific survival (p= 0.004) for stage III IMPC patients compared with stage III IDC.…”
Section: Discussionmentioning
confidence: 99%